A Mathematical Model of a Molten Carbonate Direct Carbon Fuel Cell. Issue 1 (12th December 2019) - Song, Datong; Xie, Zhong; Zhang, Xinge; Qu, Wei; Wang, Qianpu
Abstract : A one-dimensional (1D) homogeneous unit cell model was developed to study the performance of the molten carbonate direct carbon fuel cell (DCFC), which uses solid carbon as fuel and molten carbonate as electrolyte. It is the first unit cell model for the molten carbonate DCFC in which both 4-electron carbon oxidation and 2-electron CO oxidation reactions, as well as the reverse Boudouard reaction, are considered. The simulation results verify that, besides the relatively sluggish kinetics of the anodic reactions, cell performance is mainly limited by ohmic losses in the anode. Further modeling exploration reveals that a minimum effective electronic conductivity of around 0.56 S/cm is required to facilitate proper electrical conduction in the cathode to attain high DCFC performance. It was found that there are optimal volume fractions for the carbon fuel and liquid electrolyte in the anode. If the effective electronic conductivity of the cathode falls to 0.56 S/cm, optimal volume fractions also exist for the solid material and liquid electrolyte in the cathode. The detailed modeling analysis showed that performance improvement at high operating temperature was mainly attributed to improvement of anodic kinetics and reduction of ohmic loss in the electrolyte of electrodes and electrolyte matrix.